Neuroenhancement and vulnerability in adolescence - Erhardt, Julija (Array, 2019)
The very definition, scope, and practical implications of the concept of vulnerability are among the most debated questions in the field of vulnerability research. However, a consensus seems to exist regarding children and adolescents: they are generally considered vulnerable and in need of special protection due to their physical and psychological immaturity, lack of knowledge and life experience, and overall dependency on adults. The special status of this population is safeguarded in numerous legal and ethics documents. In this paper, we discuss the commercial use of transcranial direct current stimulation (tDCS), as a method that have potential to affect functioning of the brain tissue with electrical currents, but also a variety of digital methods used to influence the brain. tDCS is openly advertised, affordable and accessible, even to minors. However, changes that tDCS and similar methods could induce in developing brain tissue and consequently their interference with the normal neurodevelopmental processes could have far-reaching health ramifications and thus represent new sources of vulnerability that slip under the radar of formalized legal and ethics documents. This article discusses changes in the adolescent brain during development and address whether adolescents who would wish to use these neuroenhancement procedures should be considered vulnerable and on what grounds.